Sustentabilidade, justiça ecológica e bem viver : diálogos para a salvaguarda da sociobiodiversidade no contexto brasileiro - Kunkel, Ana Carolina Alcantarino Jardini (2016)
In a context of an increasingly complex society, with domestic interests that are sometimes conflicting, questioning arises as to what values should be subject to state shelter for the preservation of life and how they will be supported and enabled. Thus, the scenario policrise that humanity is currently exposed complains about the right a different look on life on Earth, so it is urgent to ask ourselves if the way of life of society has been sustainable. The objective is to analyze, at first, the modern Western thinking, the environmental crisis and sustainable development. Following advances in the study of injustice scenarios and content of ecological justice, as well as studying the risks arising from hydro-agribusiness model, with emphasis on the issue of pesticides, as the scenarios of environmental injustice and degradation ecological have worsened every day. Finally, sustainability is sought from the southern epistemologies, investigating the complete wellness (“bem viver”) and the rights of nature, analyzing its relationship with sociobiodiversity to, finally, study the mainstreaming of environmental good in the Federal Constitution.